Pengaruh Penerapan SIPD, Pemanfaatan Teknologi Informasi dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan : Studi Empiris Pada BPPKAD Kabupaten Sumenep - Hafila Mahruzia; Anik Yuliati (COMPETITIVE, 2022)
The purpose of this study is to determine and test empirically the effect of the Regional Government Information Systems, utilization of information technology and internal control on the quality of financial reports BPPKAD Sumenep Regency. This research used a quantitative approach, using primary data through questionnaires. The subject of this research are employees that doing accounting functions or financial administration that has worked for 2 years with a minimum last education of D3 in all majors. The samples in this study used non probability sampling with purposive sampling with total of 55 samples that met the criteria.The analysis technique in this study using multiple regression analysis with assistance software IBM SPSS Statistics 26. The result of this study indicated that (1) Regional Government Information Systems had significant negative influence toward the  quality of financial reports on BPPKAD Sumenep Regency, (2) utilization of information technology had significant positive influence toward the  quality of financial reports on BPPKAD Sumenep Regency. (3) internal control had significant positive influence toward the  quality of financial reports on BPPKAD Sumenep Regency.Keywords : Regional Government Information Systems, Utilization of information technology, Internal Control, Quality Of Financial Reports